A novel characterization method for water trees based on the transmission characteristics of complementary split ring resonators. (24th September 2021) - Xiao, Mi; Wang, Xuguang; Ma, Haoran; Zhang, Wei
Abstract: In order to achieve rapid and simple non‐destructive testing of water trees in materials, a novel water tree characterisation method based on the complementary split ring resonators (CSRR) was proposed. The characteristics of circular CSRR and rectangular CSRR were analysed in high‐frequency electromagnetic simulation software. The resonant frequency of CSRR was found to be correlated to the dielectric constant of the materials. In addition, the lumped equivalent circuit parameters of CSRRs were also calculated and simulated. The results of electromagnetic simulations and circuit simulations achieved good consistency. In the experimental part, sensors based on the two kinds of CSRRs were fabricated and were used to detect the water tree defects in low‐density polyethylene samples. The experiment results showed that the method of using CSRR sensors to detect water tree is feasible.